2008
DOI: 10.1101/gr.074070.107
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profile of tissue-dependent and differentially methylated regions (T-DMRs) in mouse promoter regions demonstrating tissue-specific gene expression

Abstract: DNA methylation constitutes an important epigenetic regulation mechanism in many eukaryotes, although the extent of DNA methylation in the regulation of gene expression in the mammalian genome is poorly understood. We developed D-REAM, a genome-wide DNA methylation analysis method for tissue-dependent and differentially methylated region (T-DMR) profiling with restriction tag-mediated amplification in mouse tissues and cells. Using a mouse promoter tiling array covering a region from −6 to 2.5 kb (∼30,000 tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
185
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(198 citation statements)
references
References 68 publications
11
185
1
1
Order By: Relevance
“…We screened for DMRs by comparing the DNA methylation profile of the PT cells with those of the whole kidney, liver, and cerebrum in a genome-wide manner (Supplemental Figure 1). 10,11 Ontology analysis of genes neighboring the DMRs revealed that the genes expressed in the kidney were significantly enriched in the genes associated with the hypomethylated DMRs in the PT cells compared with other tissues (Supplemental Tables 1 and 2). We found the enrichment of genes related to mitochondrial function and the brush border, such as Sglt2 (Slc5a2) and Glut5 (Slc2a5), in the genes with PT-DMRs (Supplemental Tables 3 and 4).…”
Section: Purification Of Pt Cells Andmentioning
confidence: 99%
See 2 more Smart Citations
“…We screened for DMRs by comparing the DNA methylation profile of the PT cells with those of the whole kidney, liver, and cerebrum in a genome-wide manner (Supplemental Figure 1). 10,11 Ontology analysis of genes neighboring the DMRs revealed that the genes expressed in the kidney were significantly enriched in the genes associated with the hypomethylated DMRs in the PT cells compared with other tissues (Supplemental Tables 1 and 2). We found the enrichment of genes related to mitochondrial function and the brush border, such as Sglt2 (Slc5a2) and Glut5 (Slc2a5), in the genes with PT-DMRs (Supplemental Tables 3 and 4).…”
Section: Purification Of Pt Cells Andmentioning
confidence: 99%
“…This observation is concordant with previous reports indicating a generally, but not exclusively, negative correlation between DNA methylation and expression. 10,25 Because we investigated DMRs in the promoter regions, the correlation of the expression and methylation levels of the DMRs located outside the promoter under diabetic conditions remains to be clarified.…”
Section: Purification Of Pt Cells Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was extracted from ES cells as described previously. 31 Genomic DNA was digested with HindIII (Takara), and 5 μg of digested DNA was denatured with 0.3 M NaOH. Sodium metabisulfite (pH 5.0) and hydroquinone were added at final concentrations of 2.0 M and 0.5 mM, respectively.…”
Section: Rt-qpcrmentioning
confidence: 99%
“…Clusters of CpGs, called CpG islands (CGIs), are often found in association with genes, most often in the promoters and first exons but also in regions more toward the 3¢ end ( Jones and Takai, 2001). Genome-scale DNA methylation analyses show that tissue-specific differentially methylated regions (tDMRs) are frequently in mammalian genomes and related to tissue-specific gene expression (Song et al, 2005;Rakyan et al, 2008;Yagi et al, 2008;Song et al, 2009).…”
Section: Introductionmentioning
confidence: 99%